Memoirs of travellers and foreign specialists as the sources of personal origin about Holodomor: informational potential - Boriak, Tetiana (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
The purpose of the article. To illustrate comprehension of Holodomor y foreign specialists who were in Ukraine during the famine and thus to introduce their testimonies into scientific information space. The research methodology. Methods of analysis and synthesis, content-analysis, bibliography heuristics and problem-thematic. The scientific novelty. The author systematizes testimonies about the famine left by foreigners. This allows correlate their experience and evaluation with the sources of personal origin and contemporary evaluation by historiography. Also foreign sources of personal origin are introduced in scientific information space. Conclusions. Given testimonies contain descriptions of the consequences of starvation visible to outsiders (cannibalism and corpse-eating, mortality, burial, emptied huts, crowds of hungry on the streets, DPU control, appearance of starving, photos of bread from starving regions). Of extreme importance is analysis provided by foreigners with high education regarding political reasons of Holodomor, politics on disinformation and militarization of society – of general artificial nature of the famine.